Antibacterial Activity and Sensory Profile of Sambong (Blumea balsamifera) Leaf Extract as a Liquid Hand Soap - Jumalon, Sophia Alexa Gamboa; Capilitan, Lester William Galacio; Tanquion, Xirxes Vhon Dela Cruz; Saldo, Ian Jay Paspe (Asian Journal of Biological and Life Sciences, 2025)
Aim/Background: Medicinal plants have long been integral to traditional healing, particularly in Asia. This study investigates the antibacterial efficacy and sensory attributes of Sambong (Blumea balsamifera) liquid hand soap, focusing on its inhibitory effects against Staphylococcus aureus (Gram-positive Bacteria) and Escherichia coli (Gram-negative Bacteria). Additionally, it assesses user perceptions regarding scent, color, and overall appeal, comparing Sambong soap to commercially available liquid hand soap. Materials and Methods: This research employs a Research and Development (R&D) approach with a quantitative experimental design involving 30 participants. Each soap sample was tested in triplicate to ensure reliability. Results: The antibacterial assessment revealed that neither Sambong nor the commercial soap exhibited inhibitory effects against E. coli. However, Sambong soap demonstrated superior antibacterial activity against S. aureus, with an average inhibition zone of 12.43±0.59 mm, compared to the commercial soap’s 10.07±1.06 mm. Given the lack of effectiveness against E. coli, further improvements are recommended to enhance activity against GNB. Sensory evaluation yielded an average rating of 2.90, categorized as moderate, indicating room for refinement in fragrance and visual appeal. Conclusion: Sambong soap consistently inhibited S. aureus, with inhibition zones measuring 11.6 mm, 12.9 mm, and 12.8 mm. The commercial soap, by contrast, exhibited inhibition zones ranging from 8.7 mm to 12.8 mm, indicating variable antibacterial efficacy. Neither soap was effective against E. coli, with a uniform 0 mm inhibition zone. Sensory evaluation scores averaged 2.90 for Sambong and 2.60 for the commercial soap, with Sambong showing greater consistency (SD=0.50) than its commercial counterpart (SD=0.76). An independent t-test found no statistically significant difference in sensory perceptions (t=1.81, p=0.076; p>0.05), suggesting that despite formulation differences, both soaps were perceived similarly regarding sensory attributes.
Keywords: Blumea balsamifera; Escherichia coli (GNB); Liquid hand soap; Sambong; Staphylococcus aureus (GPB)